Do motivations for using Facebook moderate the association between Facebook use and psychological well-being? - Rae, James R.; Lonborg, Susan D. (Frontiers in Psychology, 2015)
Previous investigations of the relationship between Facebook use and psychological well-being have most commonly considered variables relating to the quantity (e.g. time spent online) and underlying motivations (e.g. making new friends) of Facebook consumption. However, previous research has reached contradictory conclusions in that quantity of Facebook use has been linked to both higher and lower levels of psychological well-being. The current study investigated whether these contradictory findings of quantity of Facebook use could be explained by considering users’ motivations for accessing Facebook. We predicted that quantity of use would be positively associated with psychological well-being when users primarily accessed Facebook to maintain existing relationships but negatively associated with psychological well-being when primarily accessed to create new relationships. In a sample of college undergraduates (N=119), we found that the relationship of quantity of Facebook use on psychological well-being was moderated by the motivation of the user. Quantity of Facebook use was associated with higher levels of psychological well-being among users that accessed Facebook for friendship purposes but was negatively associated with psychological well-being among users that accessed for connection purposes (e.g. making new friends). We also replicated our results across dimensions of psychological well-being (e.g. anxiety and life satisfaction). The current findings provide initial evidence that quantity and motivations of Facebook use interact with potentially serious implications for psychological well-being and also provide possible explanation for why quantity of Facebook use can be linked with both positive and negative psychological well-being.